Report - Soc.of Goldsmiths, 5 May 1926
1926-05-05 "Report - Soc.of Goldsmiths, 5 May 1926" [g0603001.jpg], 5 May 1926, Society of Goldsmiths, Jewellers and Kindred Trades Union Reports and Correspondence